A reappraisal of serotype factors 4, 5 and 6 of Bordetella pertussis. - Preston, N. W. (Cambridge University Press, 1982)
Twelve strains of Bordetella pertussis, of various serotypes, were tested by agglutination with serial dilutions of six antisera which were thought by their donor to be monospecific for six distinct agglutinogens. The first three sera were shown, by agglutination of the twelve donated strains and of standard pertussis serotypes, to be monospecific for the three well-recognized major agglutinogens (factor 1, factor 2, factor 3). The 'factor 4' serum gave weak agglutination, but only of strains that possessed factor 2, though not all of such strains. This suggested that it may be a distinct minor component of factor 2. The 'factor 5' serum was very weak, and gave agglutination only with a few of the factor 2 strains. The titres of the 'factor 6' serum were very closely parallel to those of the factor 3 serum, and it may be inferred that these 'factors' probably constitute a single antigenic entity. Seven of the twelve donated strains were shown to be mixtures of two or more serotypes, offering an explanation for discrepancies in serological tests involving the use of these strains on different occasions. It seems likely that 'factors 5 and 6' do not actually exist; and, since 'factor 4' is only a minor component of factor 2, any protective role that it may have would probably be covered by the presence of factor 2 in vaccine.